Prednisolone Alters Endometrial Decidual Cells and Affects Decidual-Trophoblast Interactions - Grbac, Eliza; So, Teresa; Varshney, Swati; Williamson, Nicholas; Dimitriadis, Evdokia; Menkhorst, Ellen (Frontiers in Cell and Developmental Biology, 2021)
Poor pregnancy outcomes such as recurrent pregnancy loss and preeclampsia are associated with impaired decidualization and abnormal trophoblast invasion. Emerging evidence suggests that use of corticosteroids, including prednisolone affects fertility by altering uterine function and may be associated with preeclampsia incidence. In this study, using primary and gestational-age appropriate tissue, we aimed to define the effect of prednisolone on human endometrial stromal fibroblast (hESF) decidualization and determine whether hESF decidualization in the presence of prednisolone would alter hESF regulation of trophoblast function. We found that prednisolone treatment reduced hESF cytokine expression (IL6, IL11, IL18, LIF, LIFR) but had no effect on hESF expression or secretion of the classic markers of decidualization (prolactin and IGFBP1). Using proteomics we determined that prednisolone altered decidualized hESF protein production, enriching hESF proteins associated with acetylation and mitrochondria. Conditioned media from hESF decidualized in the presence of prednisolone significantly enhanced trophoblast outgrowth and trophoblast mRNA expression of cell motility gene PLCG1 and reduced trophoblast production of PGF. Prednisolone treatment during the menstrual cycle and 1st trimester of pregnancy might alter decidual interactions with other cells, including invasive trophoblast.